Use of complementary and alternative medicine in sports and effects of Eurycoma longifolia jack on aerobic metabolism in collegiate athletes / Lim Pei Jean - Lim , Pei Jean (2017)
The use of herbs and plants as ergogenic aids in exercise is a common practice among athletes as this complementary or alternative medicines is believed to have properties that may improve the athlete’s wellbeing and exercise performance. Locally, a traditional medicinal plant that is used to improve health and stamina is Eurycoma longifolia Jack (E. longifolia) or Tongkat Ali, however, lack of scientific evidence warrants an investigation of its acclaimed benefits in endurance exercise. The main aims of this study are to investigate the: (i) prevalence of complementary and alternative medicine among athletes in Malaysia, (ii) effect of acute and chronic consumption of E. longifolia on aerobic metabolisms during prolonged exercise, and (iii) lipid lowering effect of E. longifolia in an isolated cell culture. Complementary and alternative medicine (CAM) is a subset of medicine which is generally regarded as a practice that includes a variety of treatment methods that is not mainstream conventional medicine. Since the prevalence of its usage has not been investigated among Malaysian national athletes, a survey was carried out on 231 sportsmen to examine the practice, reasons for using, and types of CAM therapies used. The survey showed that CAM is highly used among athletes in the past 12 months, especially in female athletes. This could be attributed to weight management aspiration and to a lesser extent menstrual related problems. It was also shown that athletes who consulted conventional physicians were often prescribed acupuncture as well. In addition, both male and female athletes preferred CAM to promote recovery, particularly the use of Vitamin C supplementation, and praying for health was preferred as self-help practices. The usage of supplements was preferred because they were readily available and affordable. Interestingly, it is shown that Malaysian athletes were similar to those from other countries, who rely on CAM usage to manage their well-being. Prior studies have shown that endurance exercise capacity may be improved when fat oxidation is increased through interventions. E. longifolia has been hypothesised to improve fat metabolism and increase muscle strength during exercise, however, evidence to support these is still lacking. Using a randomised, double-blinded study, placebo-controlled design, the study investigated the acute effect of E. longifolia on aerobic metabolism in male athletes. Briefly, the athletes recruited were given either E. longifolia or placebo supplements, and ran on the treadmill for an hour at the speed based on 65% of their respectiveVO2max. The expired gas was collected and analysed for carbohydrate and fat metabolisms while blood samples were withdrawn to determine free fatty acid (FFA), glycerol, TG, glucose, insulin, cholesterol (i.e. total cholesterol, HDL, LDL), testosterone, and cortisol concentrations. An acute 3-day E. longifolia supplementation (1.7 mg/kg body weight) resulted in increased fat metabolism during the moderate intensity exercise. From the blood analyses, increased glycerol and cortisol concentrations, while decreased FFA and LDL were observed. These suggest that E. longifolia group athletes were conditioned to favour fat metabolism as an energy source compared to glucose, as seen in the PG group. It is believed that athletes who are conditioned to use fat as an energy source would have better aerobic performance. Similarly, this phenomenon was also observed in prolonged usage of E. longifolia of up to 5 weeks. Therefore, E. longifolia is shown to benefit athletes who mainly depend on aerobic performance by disproportioning the metabolism towards fat burning for better energy yield. To further examine lipid-lowering effect of E. longifolia, the study employed an in vitro model to investigate whether E. longifolia possesses lipid lowering potential or the changes was a physiological side-effect of the supplementation. The human hepatic cell line WRL-68 was treated with various concentrations (1, 2, 4 and 8 μg/ml) of the aqueous E. longifolia root extract. Results demonstrated that intracellular fatty acids build up was reduced up to ~72%, in the treated cells compared to untreated control. This study therefore, unravelled the novel potential of intracellular lipid lowering effect of E. longifolia. In conclusion, the epidemiology data of CAM practice among national athletes shows high usage mainly among female athletes. In view of improving sports performance, athletes prefer supplementation, while for self-help practice, prayers play a convincing role. These findings could also serve as one of the foundation in policy making in managing athletes. As a growing country in sports, E. longifolia can be widely used as an ergogenic aids to improve fat availability as energy source during aerobic exercise.